Improving Student’s Descriptive Writing Skill through Silent Card Shuffle Strategy - Sari, Rosi Kumala; Putri, Dwi Megista Putri; Dania, Rahma (Language Circle: Journal of Language and Literature, 2024)
This study aims to improve students’ descriptive writing skill by applying Silent Card Shuffle Strategy. The method used this research is action research. The subject was students on semester 3 from Management Class of UPI YPTK Padang. They are chosen because they are learning the English business subject on this semester and have learned simple present tense in previous semester. Writing English Skill is important for Management students for productive skill. One of them is creating the English brochure. English brochure can be as basic media for creating business for management students. Unfortunately, most of them have not master in writing English. So lecturer has chosen Silent Card Shuffle Strategy to improve the student’s English descriptive writing skill. The instruments were used to collect the data were observation, questionnaire, Students’ writing test. Then the qualitative data were grouped based on the indicators. In addition, quantitative data has analyzed by Anggoro Formula. Then the researcher interpreted the data to get the result of this research. The research shows that Silent Card Shuffle Strategy is quite good. It can improve the students ‘English descriptive writing skill. This is evidenced by the score of students’ writing test. It increases from the pretest, cycle I and cycle II. The increasing can be seen from of students ‘mean score on pretest, cycle I and II. The students mean ‘score are 50, 5 on pretest, 67, 7 on cycle I and 83, 8 on cycle 2. Thus, the application of Silent Card Shuffle Strategy can increase the students’ descriptive writing skill.